Willingness to use pre-exposure prophylaxis (PrEP) for HIV prevention among men who have sex with men (MSM) in Malaysia: findings from a qualitative study - Bourne, A.; Cassolato, M.; Thuan Wei, C.K.; Wang, B.; Pang, J.; Lim, S.H.; Azwa, I.; Yee, I.A.; Mburu, G. (Wiley Open Access, 2017)
Background: Men who have sex with men (MSM) continue to be disproportionately affected by HIV in Malaysia. Recent success has been observed within demonstration projects examining the efficacy of HIV pre-exposure prophylaxis (PrEP), an antiretroviral -based medication taken by HIV-negative men to prevent sero-conversion. In order for such promising findings to be translated in real-world settings, it is important to understand the acceptability of PrEP, including perceived barriers to access or uptake. Methods: As part of a larger mixed-methods study exploring acceptability and willingness to use PrEP among MSM in Malaysia, 19 men took part in audio-recorded focus group discussions hosted by a community-based HIV organization and facilitated by a trained researcher. Discussions focussed on awareness and potential information management, general perceptions of PrEP and potential motivations or barriers to the use of PrEP, including those at the personal, social, health system or structural level. Data were transcribed verbatim and underwent a detailed thematic analysis. Results: Rather than perceiving PrEP as a replacement for condoms in terms of having safer sex, many participants viewed it as an additional layer protection, serving as a crucial barrier to infection on occasions where condom use was intended, but did not occur. It was also perceived as more valuable to "at-risk" men, such as those in HIV sero-discordant relationships or those with a higher number of sexual partners. Elements of discussion tended to suggest that some men taking PrEP may be subject to stigma from others, on the assumption they may be promiscuous or engage in high-risk sexual behaviours. Conclusions: This qualitative study indicates that, broadly speaking, PrEP may be acceptable to MSM in Malaysia. However, in order for its potential to be realized, and uptake achieved, educative interventions are required to inform the target population as to the efficacy and potential, positive impact of PrEP. Given concerns for how those taking it may be stigmatized, it is crucial that the use of PrEP is presented as a responsible course of action, and one of a range of strategies that men can use to keep themselves safe from HIV.